2022
DOI: 10.3390/antiox11061170
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the Supercritical Impregnation of Olea europaea Leaves Extract into Filaments of Thermoplastic Polyurethane (TPU) and Polylactic Acid (PLA) Intended for Biomedical Applications

Abstract: The leaves of Olea europaea as agricultural waste represent a convenient source of antioxidants. In combination with supercritical CO2 (scCO2), assisted impregnation is an interesting strategy for the preparation of biomedical devices with specific bioactivity. For this purpose, 3D-printable filaments of thermoplastic polyurethane (TPU) and polylactic acid (PLA) were employed for the supercritical impregnation of ethanolic olive leaves extract (OLE) for biomedical application. The extraction of OLE was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…Kuska et al [ 15 ] reported an increase in thymol loading into PLA beads from 11.0 to 19.8% at 20 MPa and 120 °C by prolongation of the process from 2 to 24 h. This BC acted as a molecular lubricant, which resulted in the increased free volume of the PLA matrix and consequently in the higher sorption of a supercritical solution. The prolonged exposure of PLA to sc-CO 2 with thymol led to a 40–90% greater swelling extent in comparison to the first 2 h. A similar result was reported for the SSI of olive leaves extract into PLA filaments, where the prolongation in soaking time from 0.5 to 1 h increased both the swelling and loading [ 125 ]. However, an increase in the soaking time can also lead to a decrease in the loading of BC during the SSI process.…”
Section: Pla Impregnation With Bioactive Components Using Sc-cosupporting
confidence: 70%
See 4 more Smart Citations
“…Kuska et al [ 15 ] reported an increase in thymol loading into PLA beads from 11.0 to 19.8% at 20 MPa and 120 °C by prolongation of the process from 2 to 24 h. This BC acted as a molecular lubricant, which resulted in the increased free volume of the PLA matrix and consequently in the higher sorption of a supercritical solution. The prolonged exposure of PLA to sc-CO 2 with thymol led to a 40–90% greater swelling extent in comparison to the first 2 h. A similar result was reported for the SSI of olive leaves extract into PLA filaments, where the prolongation in soaking time from 0.5 to 1 h increased both the swelling and loading [ 125 ]. However, an increase in the soaking time can also lead to a decrease in the loading of BC during the SSI process.…”
Section: Pla Impregnation With Bioactive Components Using Sc-cosupporting
confidence: 70%
“…This process requires good solubility of the substance in question in sc-CO 2 , which facilitates its mass transport within the polymeric matrix [ 18 ]. If the solubility of a BC in sc-CO 2 is low for the PLA impregnation process, it could be improved by the addition of a polar co-solvent such as ethanol [ 124 , 125 ]. After contact between a polymeric material and a BC for a certain soaking time, sc-CO 2 can be completely removed from the obtained material by a pressure decrease, while BC will remain within the polymer matrix due to precipitation or chemical bonding [ 86 , 126 ].…”
Section: Pla Impregnation With Bioactive Components Using Sc-comentioning
confidence: 99%
See 3 more Smart Citations